2004
DOI: 10.1074/jbc.m407985200
|View full text |Cite
|
Sign up to set email alerts
|

Survivin and p53 Modulate Quercetin-induced Cell Growth Inhibition and Apoptosis in Human Lung Carcinoma Cells

Abstract: Quercetin, a ubiquitous bioactive plant flavonoid, has been shown to inhibit the proliferation of cancer cells. However, the regulation of survivin and p53 on the quercetin-induced cell growth inhibition and apoptosis in cancer cells remains unclear. In this study, we investigated the roles of survivin and p53 in the quercetin-treated human lung carcinoma cells. Quercetin (20 -80 M for 24 h) induced the cytotoxicity and apoptosis in both A549 and H1299 lung carcinoma cells in a concentration-dependent manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
0
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 40 publications
7
107
0
10
Order By: Relevance
“…The lack of response to apoptotic stimuli results in tumor growth and progression as well as resistance to most oncologic therapies [17]. It has been reported that the inhibition of apoptosis induces mitotic progression in cancer cells [18]. The suppression of apoptosis is considered one of the possible mechanisms of tumor progression, and many anti-cancer treatments act through their induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of response to apoptotic stimuli results in tumor growth and progression as well as resistance to most oncologic therapies [17]. It has been reported that the inhibition of apoptosis induces mitotic progression in cancer cells [18]. The suppression of apoptosis is considered one of the possible mechanisms of tumor progression, and many anti-cancer treatments act through their induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The main procedure was according to our previous study (32). After treatment with or without baicalein, the cells were fixed in 4% paraformaldehyde solution in PBS for 1 h at 37jC.…”
Section: Cell Number Assaymentioning
confidence: 99%
“…Western Blot Analysis The total cellular protein extracts were prepared as described (32). Western blot analyses of cyclin B1, CDC2, phospho-CDC2, survivin, p38, phospho-p38, AKT, phospho-AKT, BCL-2, XIAP, and extracellular signalregulated kinase-2 were done using specific antibodies.…”
Section: Cell Number Assaymentioning
confidence: 99%
“…In addition, Gudkov et al showed that PFT-a protected mice from the lethal genotoxic stress associated with cancer treatment without promoting the formation of tumors. As this compound was shown in subsequent in vitro and in vivo studies to protect different cell types against p53-dependent apoptosis induced by a multitude of stimuli, [5][6][7][8][9][10][11] PFT-a was considered a specific p53 inhibitor and was therefore commonly used to distinguish p53-dependent and -independent apoptosis systems. However, only a few studies applied PFT-a onto p53-deficient cells to unambiguously show its specificity in their systems.…”
mentioning
confidence: 99%